The Enthusiast$1 (Bs guide to night and low-light photography :s 50 photographic principles you need to know - Hess, Alan (Unites States of America : Rocky Nook, 2017)
The Enthusiast$1 (Bs Guide to Night and Low-Light Photography: 50 Photographic Principles You Need to Know teaches you how to shoot compelling images at night and in low-light situations. Chapters are broken down into a series of numbered lessons, with each lesson providing what you need to improve your photography. In this book, which is divided into five chapters that include 50 photographic principles to help you create great images, photographer and author Alan Hess covers all the necessary gear and camera settings, as well as topics such as light painting, photographing the night sky, shooting great cityscapes, and post-processing techniques that will bring out the best in your photographs.s
Chapter 1. Night and Low-Light Photography Basics -- 2. All the gear you will want and need -- 3. Capturing action in Low light -- 4. Low-Light portrait and Scenic Photography -- 5. Adobe photoshop post- processing techniques for low-light images. -- Index.
Includes index.
Keywords: NIGHT PHOTOGRAPHY